Law and Regulatory Certainty: An Analysis of Its Impact on the Investment Climate and Business Governance in Indonesia - Ali Huristak Hartawan Hasibuan; Nur-Amimi Tahe (Jurnal Pembangunan Hukum Indonesia, 2026)
Legal reform is an important way to create regulatory certainty which improves the investment climate and business governance in Indonesia. Yet complexity and disharmony in regulation, inconsistent policy implementation and weak institutional coordination still hinder legal certainty for businesses. The objective of this research is to analyse the implementation of legal reforms in achieving regulatory certainty, to determine the impact of the legal reform on the investment climate and business governance in Indonesia. The research uses a normative legal research approach with descriptive-analytical specifications through legislative, conceptual, and analytical approaches. The data used is in the form of secondary data obtained through literature studies, then analyzed qualitatively through the interpretation and synchronization of laws and regulations. The results of the study show that legal reform has encouraged the simplification of regulations, digitization of services, and improvement of the licensing system, but its effectiveness is still constrained by regulatory disharmonization, inconsistency of implementation, and weak institutional coordination. Regulatory certainty has been proven to increase investor confidence, support ease of doing business, strengthen the implementation of good governance, and increase national investment competitiveness. Therefore, strengthening regulatory harmonization, consistency of law enforcement, and institutional reform are the main prerequisites in creating a sustainable investment climate and more effective governance of the business world.